2023
DOI: 10.1177/00469580231209161
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Early Impacts of the COVID-19 Pandemic on Brain Injury Associations Across Canada: A Qualitative Study

Ana Paula Salazar,
Sophie Lecours,
Lisa Engel
et al.

Abstract: The COVID-19 pandemic has increased challenges for people living with brain injury and community associations to support this vulnerable population. This study aimed to gain an in-depth understanding of the challenges faced by brain injury survivors during the first year of the pandemic and how community brain injury associations adapted their services to respond to these needs. Findings from seven focus-group with 31 representatives of Canadian brain injury associations revealed 4 main themes: (1) Addressing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…In South Africa, socioeconomically vulnerable women living with HIV in South Africa reported that the pandemic affected access to HIV and family planning services. 35,36 In the US, many services were forced to suspend in-person HIV testing and various community outreach events. 37,38 Rodriguez, Martinez, Ziolkowski, Tolliver, Young, Ruiz 39 conducted a study regarding people experiencing homelessness in Indiana during the pandemic with findings speaking to the impact of disruptions of services.…”
Section: Discussionmentioning
confidence: 99%
“…In South Africa, socioeconomically vulnerable women living with HIV in South Africa reported that the pandemic affected access to HIV and family planning services. 35,36 In the US, many services were forced to suspend in-person HIV testing and various community outreach events. 37,38 Rodriguez, Martinez, Ziolkowski, Tolliver, Young, Ruiz 39 conducted a study regarding people experiencing homelessness in Indiana during the pandemic with findings speaking to the impact of disruptions of services.…”
Section: Discussionmentioning
confidence: 99%